A mini review on immune role of chemokines and its receptors in snakehead murrel Channa striatus - Bhatt, Prasanth; Kumaresan, Venkatesh; Palanisamy, Rajesh; Ravichandran, Gayathri; Mala, Kanchana; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Md. Yusoﬀ, Fatimah; Arockiaraj, Jesu (Elsevier, 2017)
Chemokines are ubiquitous cytokine molecules involved in migration of cells during inflammation and normal physiological processes. Though the study on chemokines in mammalian species like humans have been extensively studied, characterization of chemokines in teleost fishes is still in the early stage. The present review provides an overview of chemokines and its receptors in a teleost fish, Channa striatus. C. striatus is an air breathing freshwater carnivore, which has enormous economic importance. This species is affected by an oomycete fungus, Aphanomyces invadans and a Gram negative bacteria Aeromonas hydrophila is known to cause secondary infection. These pathogens impose immune changes in the host organism, which in turn mounts several immune responses. Of these, the role of cytokines in the immune response is immense, due to their involvement in several activities of inflammation such as cell trafficking to the site of inflammation and antigen presentation. Given that importance, chemokines in fishes do have significant role in the immunological and other physiological functions of the organism, hence there is a need to understand the characteristics, activities and performace of these small molecules in details.